Assessing the impact of the DIGS curriculum on agricultural literacy in youth - Appel, Sarah E., author; Enns, Kellie, advisor; Clark, Nathan, committee member; Martin, Jennifer, committee member; Bennett, Jennifer, committee member (Colorado State University. Libraries, 2022)
This research examines the impact of the DIGS curriculum on agricultural literacy, the breadth of agricultural understanding, and affinity for agriculture. The DIGS curriculum is a third thru fifth-grade curriculum emphasizing hands-on, interactive lessons in eight agricultural pathways. Students participated in each lesson and completed a supplemental activity in the DIGS booklet. This curriculum was implemented over a school year with one monthly lesson and activity. Chapter one assesses the impact of DIGS on agricultural literacy. Researchers define agricultural literacy as understanding agriculture as an integrative system built on experiences, relationships, and inspiring investment in the future of agriculture. The Longhurst Murray Agricultural Literacy Instrument (LMALI) is used to collect pre- and post-scores to evaluate the agricultural knowledge of participants. Researchers then assessed the breadth of agricultural understanding by completing a content analysis on the booklets. The breadth of understanding is broken into three themes based on the definition of agricultural literacy: (1) agriculture as a system, (2) agriculture and relationships, and (3) the future of agriculture. Researchers found that DIGS participants had increased LMALI scores after completing the curriculum, and many had evidence of a breadth of agricultural understanding. Chapter two assesses the impact of the DIGS curriculum on students' affinity for agriculture. Students responded to an affinity survey at the end of the curriculum and completed monthly activities in their DIGS booklets. Researchers performed a content analysis on the booklets and post-curriculum posters to evaluate how students felt about the curriculum and agriculture throughout the process. Researchers found that many students had or developed an affinity for agriculture during the curriculum. Many shared thoughts of wanting to participate in agricultural activities and reported that the curriculum was "fun" and that agriculture was "important." This project demonstrates the impact of the DIGS curriculum on agricultural literacy, a breadth of agricultural understanding, and affinity for agriculture. Overall, the findings show that DIGS impacted all three of these areas; increasing agricultural literacy based on knowledge, demonstrating a breadth of understanding in agriculture, and developing an affinity for agriculture throughout the curriculum.
Keywords: agricultural literacy; affinity; youth